A cohort study of adolescents with depression in China: tracking multidimensional outcomes and early biomarkers for intervention. Issue 4 (26th August 2022) - Zhang, Xiaofei; Zhou, Yanling; Sun, Jiaqi; Yang, Ruilan; Chen, Jianshan; Cheng, Xiaofang; Li, Zezhi; Chen, Xinlei; Yang, Chanjuan; Zhu, Xinhong; Cao, Liping
Abstract : Background: Depression in adolescents is recognised as a global public health concern, but little is known about the trajectory of its clinical symptoms and pathogenesis. Understanding the nature of adolescents with depression and identifying early biomarkers can facilitate personalised intervention and reduce disease burden. Aims: To track multidimensional outcomes of adolescents with depression and develop objective biomarkers for diagnosis, as well as response to treatment, prognosis and guidance for early identification and intervention. Methods: This is a multidimensional cohort study on the Symptomatic trajectory and Biomarkers of Early Adolescent Depression (sBEAD). We planned to recruit more than 1000 adolescents with depression and 300 healthy controls within 5 years. Multidimensional clinical presentations and objective indicators are collected at baseline, weeks 4, 8, 12 and 24, and years 1, 2, 3, 4 and 5. Conclusions: To the best of our knowledge, this is the first longitudinal cohort study that examines multidimensional clinical manifestations and multilevel objective markers in Chinese adolescents with depression. This study aims at providing early individualised interventions for young, depressed patients to reduce the burden of disease. Trial registration number: Chinese Clinical Trial Registry ID ChiCTR2100049066.